Effects of Neopterin on Focal Cerebral Ischemia In Rats - Arai Toshiyuki; Ishii Hisanari; Mori Hiroko; Mori Kenjiro; Kojima Shuji (Pteridines, 1996)
We examined the effects of neopterin on focal cerebral ischemia induced by transient (2 h) occlusion of the middle cerebral artery (MCA) in rats. Neopterin was administered 10 min before reperfusion (3 mg/kg i.p). The ischemic damage was evaluated one week after the MCA occlusion by magnetic resonance imaging (MRI) and by the immunohistochemical reaction for microtubule-associated protein 2 (MAP2). The ischemic lesion detected by MRI was significantly smaller in the neopterin-treated group than in the non-treated group (n=4 in each group, p<0.05). However, the ischemic neuronal damage determined by MAP2 in the neopterintreated group was not significantly different from that in the non-treated group. Since MRI is thought to reflect the distribution of not only neurons but also glial cells, these results may indicate the effects of neopterin on the glial reaction in focal cerebral ischemia.